Identification of equilibrium state of hydroxyl protons in vodkas by 1H NMR spectroscopy - Kuzmin, Oleg; Sujkov, Sergey; Koretska, Iryna; Matyiashchuk, Olena; Polovyk, Volodymyr (My University, 2017)
The conducted researches set a fundamental difference of behavior of hydroxyl proton of ethanol and water in vodkas, using 1H NMR spectroscopy.
Keywords: горілка; етанол; вода; гідроксил; 1H ЯМР спектроскопія; водка; этанол; гидроксил; ethanol; water; hydroxyl; 1H NMR spectroscopy; кафедра технології ресторанної і аюрведичної продукції